Analisis Faktor-Faktor Penghambat Terbitnya Surat Persetujuan Berlayar (SPB) pada Keberangkatan Kapal MT. Samudra Sindo 38 di PT. Taraka Samudra Sejahtera - Ahmatul Ilmi Abdullah; Trisnowati Rahayu; Diyah Purwitasari; Elly Kusumawati (JURNAL RISET MANAJEMEN (JURMA), 2024)
Port clearance is an important document for ships that will sail. However, in practice, the issuance of port clearance often experiences problems and obstacles. This research aims to determine inhibiting factors, as well as efforts to optimize the issuance of SPB or port clearance. This research uses a qualitative research method with a descriptive data analysis technique using the fishbone method, and data collection techniques through interviews, documentation, and observations as research data. Referring to the research results, it shows that factors such as negligence in monitoring ship documents and ineffective communication cause delays in the SPB verification and issuance process, which have an impact on delayed ship departure schedules and increased operational costs. Efforts that can be made to mitigate the consequences of the delay in the departure of MT. Samudra Sindo 38 are efforts to improve ship document monitoring and improve internal and external communication to help optimize the SPB issuance process. Thus, these steps are expected to improve the efficiency and effectiveness of SPB issuance at PT. Taraka Samudera Sejahtera.